Metastable Evaporation of Molecules from Water Clusters - Poterya, Viktoriya; Pysanenko, Andrij; Fárník, Michal; Fedor, Juraj; Hansen, Klavs (The journal of physical chemistry. A, 2024)
We probe the stability of water clusters by means of their metastable decay probability extracted from two-dimensional reflectron time-of-flight mass spectra. Two different methods are used to ionize and potentially excite the clusters and trigger the evaporation: (i) attachment of electrons with near-zero energies, producing negatively charged (H2O)n- clusters, and (ii) electron impact ionization, producing protonated (H2O)nH+ clusters. The electron attachment is a soft ionization and therefore provides information about the size distribution of the neutral clusters in the beam due to a very limited amount of post-ionization loss of water molecules. A dependence of metastable fractions on the conditions of neutral clusters production prior to the electron attachment is reported. For the cations, the higher energy electron impact ionization leads to a more extensive metastable loss of water molecules. The results are discussed in the light of neutral cluster excitation energy distributions and, for negative clusters, also in terms of binding energies. The experiments demonstrate clearly the role of the excess electron vs the excess proton in the two different charge states of the clusters around sizes N = 50-55, for which binding energies of the anions are derived from the data.